2001
DOI: 10.1002/gps.447
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation predicts re‐hospitalization in a group of older American veterans enrolled in the UPBEAT Program

Abstract: When controlling for other covariates, social isolation, physical health and mental health were significant risk factors for re-hospitalization. These findings underline the importance of assessing and addressing lack of social support, along with other factors, in the health care of older male veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 34 publications
(54 reference statements)
1
76
0
1
Order By: Relevance
“…English, Cantonese). In this way, residents felt more at home and a sense of belonging to the apartment community and able to develop social roles and social ties which are so vital to good quality of life (Victor et al, 2009;Mistry et al, 2001). …”
Section: Working Towards Ageing Well In and Around Rosewood Towersmentioning
confidence: 99%
“…English, Cantonese). In this way, residents felt more at home and a sense of belonging to the apartment community and able to develop social roles and social ties which are so vital to good quality of life (Victor et al, 2009;Mistry et al, 2001). …”
Section: Working Towards Ageing Well In and Around Rosewood Towersmentioning
confidence: 99%
“…17 Researchers in Los Angeles found that social isolation among older people was linked with a four-to five-fold increase in the likelihood of re-hospitalization within the year. 18 …”
Section: Effects On Service Utilizationmentioning
confidence: 99%
“…One-third of older adults were living alone, and almost one-half were separated, widowed, or divorced, all of which indicate increased risk for social isolation, which is a risk factor for suicide, 47 psychiatric rehospitalization, 48 and medical rehospitalization. 49 Thus the population of older adults admitted to APUs may have a high need for social supports and postdischarge psychiatric care to prevent recurrence of symptoms.…”
Section: Discussionmentioning
confidence: 99%